STRATEGIC PLANNING OF SUSTAINABLE DEVELOPMENT OF AGRICULTURE OF LAJKOVAC MUNICIPALITY - Mihailović, Branko; Simonović, Zoran; Brzaković, Tomislav (Economics of Agriculture, 2018)
The paper explores the agricultural potential of the municipality for Lajkovac and accordingly defnes the development priorities and strategic measures of sustainable development in this area. The purpose of the research is to examine the real possibilities for the development of agriculture and rural areas of the Municipality. Consequently, the analysis focuses on: the structure of the economy of the Municipality, the importance and role of agriculture and agro-industry in the municipal economy and the development priorities and strategic measures in the agriculture of the municipality. The researchs results show that the Municipality of Lajkovac has favorable factor conditions for the development of agriculture. With regard to the development of Lajkovac agriculture in the coming period, it will be important to develop the processing sector, that is, capacity building, especially in the small and medium enterprises in agriculture (SMEA) sector, in the feld of processing meat, milk, fruit and vegetables.